1976
DOI: 10.1084/jem.144.5.1227
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of leukocyte chemotaxis by human IgA myeloma components.

Abstract: Materials and MethodsCell Preparation, Chemotaxis, and Random Mobility. Human polymorphonuclear leukocytes (PMNs) were prepared from peripheral blood of healthy adult donors. Blood was mixed with heparin, 10 U/ml, to prevent coagulation. Neutrophil preparations were obtained as previously described (2, 5-7) by Plasmagel sedimentation of erythrocytes and resuspension of leukocytes to a concentration of 7 x 106 PMNs/ml in Hanks' balanced salt solution (HBSS). In some experiments mononuclear cells were removed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(90 citation statements)
references
References 20 publications
2
86
0
1
Order By: Relevance
“…As noted, some studies have suggested an anti-inflammatory function for IgA and Fc␣RI, as demonstrated in the suppression of neutrophil chemotaxis, down-regulation of the generation of reactive oxygen species, and the induction of the anti-inflammatory cytokine IL-1ra (32,34). Because IgA in the serum does not fix complement by the classical pathway, IgA is thought to act as a "discrete housekeeper" in which foreign Ags are incorporated into immune complexes by IgA and removed by the phagocytic system, with little or no resultant inflammation (57).…”
Section: The Ser 248 and Gly 248 Alleles Of Fc␣ri Affect Receptor Medmentioning
confidence: 92%
See 1 more Smart Citation
“…As noted, some studies have suggested an anti-inflammatory function for IgA and Fc␣RI, as demonstrated in the suppression of neutrophil chemotaxis, down-regulation of the generation of reactive oxygen species, and the induction of the anti-inflammatory cytokine IL-1ra (32,34). Because IgA in the serum does not fix complement by the classical pathway, IgA is thought to act as a "discrete housekeeper" in which foreign Ags are incorporated into immune complexes by IgA and removed by the phagocytic system, with little or no resultant inflammation (57).…”
Section: The Ser 248 and Gly 248 Alleles Of Fc␣ri Affect Receptor Medmentioning
confidence: 92%
“…Unlike Fc␥RIII and Fc RI, however, Fc␣RI is often expressed in the absence of ␥-chain pairing (26,27) and the function of this nonpaired Fc␣RI has not been defined. Indeed, the net function of Fc␣RI per se is unresolved, with some investigators reporting a capacity to initiate a proinflammatory program (28 -30) while others report a noninflammatory profile (31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…A modification of the Boyden technique with 5-,um pore size membranes (Sartorius Filters, Inc., S. San Francisco, Calif.) to separate the upper cell suspension compartment and the lower chemotactic factor compartment was used to assess PMN chemotaxis (16). The PMN suspension, 0.4 ml at 7.0 x 106 PMN/ml, was placed in the upper compartment and chemotactic factor plus a 10% serum test sample in the lower 0.25 ml compartment.…”
Section: Methodsmentioning
confidence: 99%
“…37 We have demonstrated for the first time that monovalent targeting of FcaRI by mIgA inhibits IgG-mediated phagocytosis in human monocytes, 30 which explains the previously reported inhibitory functions of serum mIgA. [23][24][25][27][28][29] More importantly, we have been able to show that FcaRI-mediated inhibition is not mediated by conventional inhibitory motifs such as the immunoreceptor tyrosine-based inhibition motif. While c-less FcaRI recycles mIgA, thus playing an essential role in mIgA homeostasis, FcRc-associated FcaRI mediates either activating or inhibitory responses.…”
Section: Iga Receptorsmentioning
confidence: 55%
“…22 Several groups have demonstrated that in the absence of antigen, serum IgA downregulates IgG-mediated phagocytosis, chemotaxis, bactericidal activity, oxidative burst activity and cytokine release. [23][24][25][26][27][28][29] These IgA monomers may initiate FcaRImediated non-inflammatory responses against bacteria that breach the mucosal barrier. 30 Another piece of data supporting the inhibitory role of serum mIgA is the observation that selective IgA-deficient patients frequently present allergies and autoimmunity.…”
Section: Structure Of Igamentioning
confidence: 99%